2009
DOI: 10.1080/01635580902846593
|View full text |Cite
|
Sign up to set email alerts
|

Folate Intake and Prostate Cancer Risk: A Case-Control Study

Abstract: Folate deficiency has been implicated in the carcinogenesis of several tumor types. The role of folate in prostate cancer remains indeterminate. We investigated folate as a risk factor for prostate cancer among 140 biopsy-confirmed prostate cancer patients, 230 age-matched clinic controls, and 250 negative prostate biopsy controls. Dietary folate intake was inversely associated with overall risk of prostate cancer as compared to clinic controls (P for a linear trend = 0.003). When stratified by disease severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 28 publications
2
18
2
Order By: Relevance
“…Alcohol is known to interfere with folate absorption [35]; thus, we might expect to see a protective effect associated with higher folate intakes for men with high alcohol consumption, which was not apparent in our study. Our findings are in contrast to the reduced risks reported by an Italian case-control study (although the overall interactions were not significant) [10] and null associations reported by others [2,4,8,12,16].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Alcohol is known to interfere with folate absorption [35]; thus, we might expect to see a protective effect associated with higher folate intakes for men with high alcohol consumption, which was not apparent in our study. Our findings are in contrast to the reduced risks reported by an Italian case-control study (although the overall interactions were not significant) [10] and null associations reported by others [2,4,8,12,16].…”
Section: Discussioncontrasting
confidence: 85%
“…Studies investigating associations between B vitamins and prostate cancer risk have mainly focused on folate and vitamin B12, and a recent meta-analysis concluded that there were positive associations with circulating levels [2], consistent with dietary studies of vitamin B12 [3,4], whereas other studies of either intake or blood levels of folate have been inconclusive [3][4][5][6][7][8][9][10][11][12][13][14]. Associations between other B vitamins and prostate cancer risk have been less widely studied, and findings are inconsistent [3,4,8,10,15,16].…”
Section: Introductionmentioning
confidence: 91%
“…Six of these studies were already included in our review, as they also contained groups with daily intakes ≥0.4 mg,32–34 36–38 and five were excluded from our main analyses due to daily dose of folic acid below 0.4 mg 49 50 54–56. No increased risk was found in the meta-analyses of doses below 0.4 mg/day, with RR of 1.07 (95% CI 0.92 to 1.26) for the cohort studies33 34 36–38 49 50 54 56 and 1.17 (95% CI 0.58 to 2.33) for the case–control studies 32 55. Hence, our analyses did not indicate any dose–response pattern between folic acid dose and cancer incidence.…”
Section: Discussionmentioning
confidence: 91%
“…Presumably, the effects of these SNP manifests in cooperation with environmental factors, for example, level of consumption of group B vitamins and methionine. Associations of a high level of folate consumption with a lower risk of PC [8,10] and of high consumption of vitamin B 12 with a higher risk of this disease [5,14] have been described. The effects of these factors should be taken into consideration in further studies.…”
Section: Resultsmentioning
confidence: 97%